Functional validation to explore the protective role of miR-223 in Staphylococcus aureus-induced bovine mastitis - Xueqin Liu; Siyuan Mi; Gerile Dari; Siqian Chen; Jiuzhou Song; David E. MacHugh; Ying Yu (Journal of Animal Science and Biotechnology)
Abstract Background Mastitis caused by Staphylococcus aureus (S. aureus) is one of the most intractable problems for the dairy industry, causing significantly reduced milk yields and early slaughter of cows worldwide. MicroRNAs (miRNAs) can post-transcriptionally regulate gene expression and studies in recent years have shown the importance of miRNA-associated gene regulation in S. aureus-induced mastitis. Results In this study, to investigate the role of miR-223 in mastitis, we performed experiments to overexpress and suppress miR-223 in an immortalized bovine mammary epithelial cell line (MAC-T) infected with S. aureus. Overexpression of miR-223 in MAC-T cells repressed cell apoptosis and necrosis induced by S. aureus infection, whereas suppression of miR-223 had the opposite effect. Transcriptome expression profiling with weighted gene co-expression network analysis (WGCNA) and gene set variation analysis (GSVA) showed that miR-223 affects apoptosis and inflammation-related pathways. Furthermore, differentially expressed (DE) genes were evaluated, and genes exhibiting contrasting expression trends in the miR-223 overexpressed and suppressed groups were assessed as potential target genes of miR-223. Potential target genes, including CDC25B, PTPRF, DCTN1, and DPP9, were observed to be associated with apoptosis and necroptosis. Finally, through integrative analysis of genome-wide association study (GWAS) data and the animal quantitative trait loci (QTL) database, we determined that target genes of miR-223 were significantly enriched in single-nucleotide polymorphisms (SNP) and QTLs related to somatic cell count (SCC) and mastitis. Conclusion In summary, miR-223 has an inhibitory effect on S. aureus-induced cell apoptosis and necrosis by regulating PTPRF, DCTN1, and DPP9. These genes were significantly enriched in QTL regions associated with bovine mastitis resistance, underscoring their relevance in genetic regulation of disease resilience. Our findings provide critical genetic markers for enhancing mastitis resistance, particularly S. aureus-induced mastitis, through selective breeding. This work offers valuable insights for developing cattle with improved resistance to mastitis via targeted genetic selection.